P and S Wave Tomography Beneath the SE Tibetan Plateau: Evidence for Lithospheric Delamination. Issue 10 (14th October 2019) - Huang, Zhouchuan; Wang, Liangshu; Xu, Mingjie; Zhao, Dapeng; Mi, Ning; Yu, Dayong
Abstract: The SE Tibetan Plateau is located between the eastern Himalayan syntaxis and the stable Yangtze craton; its tectonic evolution is important for understanding the plateau expansion. However, interactions between the plateau and its adjacent subduction zone and craton are still unclear. In this study, we determine updated high‐resolution P and S wave tomographic models of the crust and upper mantle beneath the SE Tibetan Plateau. We confirmed the existence of a high‐velocity layer in the upper mantle down to 200‐km depth beneath the Sichuan basin, the core of the Yangtze craton, representing the stable cratonic root. Another high‐velocity body is located beneath Burma, reflecting the subducting Indian slab in the upper mantle and possibly the remnant Burman slab in the mantle transition zone. A strong low‐velocity column exists above the high‐velocity body in the transition zone and reaches the Moho under the Tengchong volcano. In addition, we find high‐velocity fragments in the upper mantle beneath the Yangtze craton and northern Indochina, which may reflect delaminated lithosphere beneath the SE Tibetan Plateau. The lithospheric delamination may be closely related to mantle flow extruded from the high plateau and possible thermal upwelling from the lower mantle. Our results provide new insight into the deep interactions between the Tibetan plateau and its surrounding blocks near the SE plateau margin. Key Points: New high‐resolution P and S wave tomography beneath the SE Tibetan Plateau Layered high‐velocity anomalies beneath the Yangtze craton and the Indochina block Lithospheric delamination beneath the SE Tibetan Plateau